2013
DOI: 10.1371/journal.pone.0062409
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Gut Microbiota in People with Different Levels of Ginsenoside Rb1 Degradation to Compound K

Abstract: Panax ginseng (family Araliaceae) which contains ginsenoside Rb1 as a main constituent is traditionally used as a remedy for cancer, inflammation, stress, and ageing. The ginsenoside Rb1 in orally administered ginseng is metabolized to bioactive compounds by gut microbiota before their absorptions to the blood. However, its metabolizing activities in individuals are significantly different as we previously demonstrated. Here, we selected 5 samples with fecal activity potently metabolizing ginsenoside Rb1 to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 27 publications
4
64
1
2
Order By: Relevance
“…2,3 Therefore, gut microbiota plays an important role in energy balance, 4,5 glucose metabolism, 6,7 low-grade inflammation 8,9 and drug metabolism. 10, 11 Recently, we found that gut microbiota-derived lipopolysaccharide (LPS) involves in the onset and progression of inflammation and metabolic diseases. 6 For example, high-fat diets increase gram-negative bacteria, which induce the production of LPS in the intestine and cause inflammation, obesity, and cancer.…”
Section: Introduction Hmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Therefore, gut microbiota plays an important role in energy balance, 4,5 glucose metabolism, 6,7 low-grade inflammation 8,9 and drug metabolism. 10, 11 Recently, we found that gut microbiota-derived lipopolysaccharide (LPS) involves in the onset and progression of inflammation and metabolic diseases. 6 For example, high-fat diets increase gram-negative bacteria, which induce the production of LPS in the intestine and cause inflammation, obesity, and cancer.…”
Section: Introduction Hmentioning
confidence: 99%
“…6,10 Therefore, to maintain a healthy condition, LPS production of gut microbiota should be decreased.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in recent studies of the human colonic microbiota, Oscillibacter has been consistently detected at the genus level, and O. valericigenes has been detected at the species level in one study, using 16S rRNA-based analysis (11)(12)(13)(14). Oscillibacter species have now been isolated from the rumen of cattle in Korea and from the alimentary canal of clams in Japan and have been identified in 16S rRNA gene clone libraries from broilers in China (15).…”
mentioning
confidence: 99%
“…Additionally, the intestinal metabolism of ginsenosides was found to be dependent on an individual's intestinal microflora making oral absorption of Rg1 and Rb1 inconsistent [31]. However, CK, a major metabolite of ginsenosides, was readily absorbed from the gastrointestinal tract independent of the parent compounds [32].…”
Section: Discussionmentioning
confidence: 99%